Addition of Trastuzumab Deruxtecan to Selpercatinib in a Patient With RET Fusion-Driven NSCLC and an Acquired HER2 Amplification: Case Report - Chetan V. Vakkalagadda, MD; Jyoti D. Patel, MD (JTO Clinical and Research Reports, 2023)
Despite the high activity of selective RET inhibitors in RET-driven NSCLC, resistance eventually develops and there is unmet need to better define therapeutic options for patients. This is a case of a patient initially thought to have no targetable alterations, then found to have a RET fusion, and subsequently HER2 amplification on three distinct biopsies. She was treated initially with chemotherapy and immune therapy, then switched to selpercatinib, and eventually had fam-trastuzumab deruxtecan added to selpercatinib. She also developed neuroendocrine differentiation at time of progression in the context of a p53 mutation, which is a known factor that can lead to small cell transformation. This patient’s case highlights the need for comprehensive molecular testing at both diagnosis and progression, as unexpected resistance mechanisms may be identified particularly for patients with uncommon driver mutations.